2020
DOI: 10.1210/clinem/dgaa248
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Type 2 Diabetes Following a Short-term Intervention With Insulin Glargine, Metformin, and Dapagliflozin

Abstract: Objective To examine diabetes remission following a short-term intensive metabolic intervention combining lifestyle and glucose-lowering approaches. Methods We conducted an open-label, randomized controlled trial in 154 patients with type 2 diabetes up to 8 years in duration on 0 to 2 glucose-lowering medications. Participants were randomized to (a) a 12-week intensive intervention comprising lifestyle approaches and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…4,5 There is currently considerable interest in strategies that aim to achieve remission or regression of diabetes through early intervention with intensive lifestyle modification or pharmacotherapy. [6][7][8][9][10][11] The pathophysiological basis of this approach lies in the existence of a reversible component to beta-cell dysfunction that is evident early in the course of T2D (but may not be present later in the natural history). 12 However, this strategy holds both promise and potential limitations, as illustrated by the example of short-term intensive insulin therapy (IIT).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 There is currently considerable interest in strategies that aim to achieve remission or regression of diabetes through early intervention with intensive lifestyle modification or pharmacotherapy. [6][7][8][9][10][11] The pathophysiological basis of this approach lies in the existence of a reversible component to beta-cell dysfunction that is evident early in the course of T2D (but may not be present later in the natural history). 12 However, this strategy holds both promise and potential limitations, as illustrated by the example of short-term intensive insulin therapy (IIT).…”
Section: Introductionmentioning
confidence: 99%
“… 71 In the DiRECT study, to maintain the lost weight, the authors changed participants’ meal patterns variously. 72 In the case of pharmacotherapy, some patients with early diabetes were able to achieve remission after short-term intensive medical therapy, 73 but limited in incretin therapies. There is no study yet on whether remission is maintained after withdrawal of the drug; therefore, lifetime therapy may be required to maintain weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been consistently reported that more than half of patients can achieve remission with recent treatment methods that induce active glycemic control and significant weight loss ( Tables 2 - 4 ). New diabetes drugs with significant weight loss effects have recently been developed and are expected to help patients achieve remission of T2DM [ 23 , 24 ].…”
Section: Strategies For the Remission Of Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…This class of drugs can reduce weight and visceral fat because it is associated with urinary glucose excretion that causes caloric loss [ 86 ]. In a clinical trial using SGLT2 inhibitors in addition to basal insulin and metformin as an intensive intervention, the intervention group with SGLT2 inhibitors achieved more remission than compared to the conventional group (24.7% vs. 16.9%), and reduced the risk of diabetes recurrence by 43% [ 23 ].…”
Section: Strategies For the Remission Of Type 2 Diabetes Mellitusmentioning
confidence: 99%